Reassessing Consumer Protection in Digital Markets: Information Asymmetry as Epistemic Injustice in Indonesia and the Philippines - Nurlaily Nurlaily; David Tan; Febri Jaya; Nur Fatihah (Vifada Assumption Journal of Law, 2025)
Purpose: This study examines whether information asymmetry in digital markets can be understood as a form of epistemic injustice and to assess how the consumer protection frameworks of Indonesia and the Philippines respond to this problem. Research Design and Methodology: This research employs the normative legal research method and comparative approach, with epistemic injustice as the main philosophical, analytical lens. To supplement the analysis, the study utilizes key primary law sources, namely Law No. 8 of 1999 and Government Regulation No. 80 of 2019 from Indonesia; and Republic Act No. 7394 and the Internet Transaction Act of 2023 from the Philippines. Findings and Discussion: Information asymmetry is comprehensively identified as a form of testimonial and hermeneutical injustice that undermines consumers’ capacity as knowers. Normative analysis conclusively shows that both countries are reliant on general legal norms, incapable of philosophically and normatively capturing information asymmetry in today’s markets. In addition, deficiencies are also found in recent regulations, where algorithmic opacity and complaint-handling mechanism remain unaddressed. Implications: The study implies the need for comprehensive reform and proposes that legal development should move beyond broad fairness principles to operationalize specific digital safeguards, and clearer disclosures, along with verifiability and platform accountability standards.